2016
DOI: 10.5455/medarh.2016.70.97-100
|View full text |Cite
|
Sign up to set email alerts
|

Time of Occurrence and Duration of Atrial Fibrillation Following Coronary Artery Bypass Grafting

Abstract: Introduction:Dilatation of the left atrium and left ventricular diastolic dysfunction (DDLV) according to recent studies has significance in the occurrence of postoperative atrial fibrillation (AF), stroke and death. Authors of some studies found no relationship between these parameters and atrial fibrillation.Objective:this study is to determine the time of occurrence and duration of atrial fibrillation in patients after surgical revascularization (CABG) due to the presence of left ventricular diastolic dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Four studies were excluded from the meta-analysis because of insufficient data provided in the articles to perform a metaanalysis. 43,[45][46][47] The cumulative Cohen's d obtained from the meta-analysis was 0.8 (95% CI: 0.6-1.0). Figure 5B shows the average LAVI measured in the studies included in the meta-analysis.…”
Section: Meta-analysis For Left Atrial Volume Indexed For Body Surfacementioning
confidence: 94%
See 1 more Smart Citation
“…Four studies were excluded from the meta-analysis because of insufficient data provided in the articles to perform a metaanalysis. 43,[45][46][47] The cumulative Cohen's d obtained from the meta-analysis was 0.8 (95% CI: 0.6-1.0). Figure 5B shows the average LAVI measured in the studies included in the meta-analysis.…”
Section: Meta-analysis For Left Atrial Volume Indexed For Body Surfacementioning
confidence: 94%
“…Twenty-seven studies investigated pre-operative left atrial volume indexed for body surface (LAVI) as a potential predictor of POAF (Table 3). [6][7][8][9][10][11][20][21][22][23][24][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Twenty-three studies were included in the continuous variables meta-analysis using random effects model (Figure 3). Four studies were excluded from the meta-analysis because of insufficient data provided in the articles to perform a metaanalysis.…”
Section: Meta-analysis For Left Atrial Volume Indexed For Body Surfacementioning
confidence: 99%
“…Currently, the most widely used echocardiographic measurement in the clinic for predicting AF is the maximal volume of the left atrium (LAVmax) 6 . Several studies have found that functional measurements of the left atrium (LA), such as the LA emptying fraction (LAEF) and the LA minimum volume index (LAVmin), are useful in predicting AF 7,8 . Since it seems that the LA functional measures can play a role in predicting AF, we hypothesized that: (1) The LA functional measurements would be better predictors than LAVmax for AF following CABG.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several studies have found that functional measurements of the left atrium (LA), such as the LA emptying fraction (LAEF) and the LA minimum volume index (LAVmin), are useful in predicting AF. 7,8 Since it seems that the LA functional measures can play a role in predicting AF, we hypothesized that: (1) The LA functional measurements would be better predictors than LAVmax for AF following CABG.…”
Section: Introductionmentioning
confidence: 99%